Shooting at a Moving Target: The Complexity of Evaluating and Monitoring the Adaptive Capacity to Climate Change of Local Government Institutions in South Africa: A Study of the Eastern Cape Province. - Gadu, Siyaxola Ernest (University of the Witwatersrand, Johannesburg, 2024)
It is no longer a myth that natural catastrophic events associated with varying climate are increasing globally, with severe and devastating consequences in poor countries, particularly in Sub-Saharan Africa, where many of the world’s poor people reside. Thus, the emphasis on adapting to varying climate is no longer optional, or a deferred problem into the future, but rather an urgent matter of concern which must be considered to be a policy priority. Countering the retrogressive climate variation challenges on economic development and ecological degradation, the South African government has, in the last two and half decades, embarked on the progressive formulation of different policy instruments and strategic frameworks to curb and minimise the effects of climate variation on all economic sectors. Applying research techniques from the qualitative research approach and existing literature, this research explored the complexities of evaluating the institutional adaptive capacity to climate change in municipal institutions of South Africa, with particular focus on the Eastern Cape Province. The research outcomes indicate that, although much remains to be achieved, some level of success has been realised, particularly in the space of policy formulation, albeit with a poor record of implementation. While the policy sounds good and is solution-driven, the implementation of the programme at local levels to achieve the desired goals, however, remains a significant challenge due to institutional and capacity challenges. In addition, the research further highlighted the fragmented climate change governance system which has posed significant systemic challenges, and these have tended to constrain decision-making and implementation processes. The institutional and capacity challenges create an unconducive environment for adequate coping strategies, and an evaluation of institutional adaptive capacity at municipal level across the country. The study findings also stressed the prominence of indigenous knowledge, and the alliance between the opportunities presented by climate variation and Sustainable Development Goals. This study further emphasized the importance of developing a reliable system to assess and monitor the institutional coping capacity at municipal level that can compare adaptive capacity of different institutions and assist in resource allocation
A research report submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Geography, Archaeology and Environmental Science, University of the Witwatersrand, Johannesburg, 2023
Keywords: Climate change adaptation; Climate change governance; Institutional adaptive capacity; Institutional reforms; Climate resilience; UCTD; SDG-13: Climate action